Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper for Belgium evaluates whether price increases in Belgium are excessive. It assesses the household and bank balance sheets and their vulnerability to a slowdown in housing prices, and identifies differences in real estate markets between Belgium and other countries. The paper analyzes policy and institutional factors that may have contributed to housing price developments in Belgium. It identifies potential policies that are available to avert a buildup of pressures. The paper also describes the model setup and calibration of some crucial economic relations and parameters.